“I Feel Like a Real Teacher”: Emergent Professionalism of Indonesian Pre-Service Teachers of English - Subekti, Adaninggar Septi (Premise: Journal of English Education and Applied Linguistics, 2022)
The present study investigated how Indonesian pre-service English teachers' professionalism emerged during their teaching practice. The study employed a qualitative document analysis of secondary data in the form of 26 student teachers' reflections from 13 pre-service teacher participants taking Micro Teaching class in the 6th semester of their study. From Thematic Analysis, the study found several themes in their emerging professionalism. First, they realized the role of teacher-student rapport for instructional success and the need to adjust instructions to suit their students' needs and proficiency levels. They could overcome stereotypes and negative preconceptions about teaching vocational students and students with special needs. They reported their joy of being acknowledged by their students as teachers, and they felt happy and proud when they saw their students' success in learning. These indicated the shift in concerns from self to students, signaling the participants' emergent professionalism. Based on the findings, possible contributions and suggested directions for future studies were mentioned, along with the study's possible limitations.